2015
DOI: 10.1371/journal.pone.0125819
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy and Phylogenetic Relationships of “Pelorosaurus“ becklesii (Neosauropoda, Macronaria) from the Early Cretaceous of England

Abstract: The sauropod dinosaur “Pelorosaurus” becklesii was named in 1852 on the basis of an associated left humerus, ulna, radius and skin impression from the Early Cretaceous (Berriasian-Valanginian) Hastings Beds Group, near Hastings, East Sussex, southeast England, United Kingdom. The taxonomy and nomenclature of this specimen have a complex history, but most recent workers have agreed that “P.” becklesii represents a distinct somphospondylan (or at least a titanosauriform) and is potentially the earliest titanosau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(124 citation statements)
references
References 111 publications
11
111
2
Order By: Relevance
“…The anteromedial proximal process is longer than the anterolateral process (ratio =1.35). This value is similar to many sauropods, but is considerably lower than in the brachiosaurids Cedarosaurus and Venenosaurus (Mannion et al, 2013; Upchurch, Mannion & Taylor, 2015). In anterior view, the articular surface of the anteromedial proximal process is not concave, differing from the morphology seen in most titanosaurs (Upchurch, 1995; Upchurch, 1998), as well as some non-titanosaurian taxa, e.g., Giraffatitan (D’Emic, 2012).…”
Section: Description and Comparisonssupporting
confidence: 67%
See 1 more Smart Citation
“…The anteromedial proximal process is longer than the anterolateral process (ratio =1.35). This value is similar to many sauropods, but is considerably lower than in the brachiosaurids Cedarosaurus and Venenosaurus (Mannion et al, 2013; Upchurch, Mannion & Taylor, 2015). In anterior view, the articular surface of the anteromedial proximal process is not concave, differing from the morphology seen in most titanosaurs (Upchurch, 1995; Upchurch, 1998), as well as some non-titanosaurian taxa, e.g., Giraffatitan (D’Emic, 2012).…”
Section: Description and Comparisonssupporting
confidence: 67%
“…In anterior view, the articular surface of the anteromedial proximal process is not concave, differing from the morphology seen in most titanosaurs (Upchurch, 1995; Upchurch, 1998), as well as some non-titanosaurian taxa, e.g., Giraffatitan (D’Emic, 2012). The posterior proximal process is much smaller than the other proximal processes, lacking the ‘T’ shaped proximal end outline that characterizes many titanosaurs (Upchurch, Mannion & Taylor, 2015). …”
Section: Description and Comparisonsmentioning
confidence: 99%
“…In sauropods, this extinction is focused on broad-toothed non-neosauropod eusauropods and narrow-toothed diplodocids , with just two occurrences known from the Cretaceous (Gallina et al, 2014;McPhee et al, 2016), and is followed by the diversification of rebbachisaurids and titanosauriforms . The earliest Cretaceous therefore represented a 'transitional' phase in sauropod evolution (Upchurch et al, 2015b), a pattern also found in Asia, with the replacement of non-neosauropods by titanosauriforms across the J/K boundary (Wilson & Upchurch, 2009;Mannion et al, 2013).…”
Section: (C) Additional Environmental Changes That Require Explorationmentioning
confidence: 91%
“…This pattern is geographically focused in taxa from Europe and North and South America, with Africa and Asia relatively unaffected . However, the precise details and magnitude of this diversity reduction are obfuscated by relatively poor preservation, sampling, and dating of earliest Cretaceous dinosaur-bearing terrestrial exposures, particularly in Gondwana, North America, and Asia Upchurch, Mannion & Taylor, 2015b; Fig. 5A).…”
Section: (3) Vertebrates (A) Dinosaursmentioning
confidence: 99%
See 1 more Smart Citation